Fate’ or ‘destiny’? Finding the subtle differences with a corpus-based technique - Nateethorn Narkprom; Supakorn Phoocharoensil (Studies in English Language and Education, 2026)
The nouns ‘fate’ and ‘destiny’ are terms often used interchangeably despite their underlying conceptual differences and are generally treated as synonyms by English dictionaries, such as the Longman Dictionary of Contemporary English and Webster’s Dictionary of American English, based on their loosely defined meanings. This study adopted a corpus-based approach, using the Corpus of Contemporary American English (COCA) as the data source. It focused on quantitative and qualitative analyses of the target synonyms in relation to their distributional, collocational, semantic, and prosodic patterns. The results reveal that ‘fate’ is mainly distributed in fiction, while ‘destiny’ appears primarily in TV/movie subtitles, indicating a moderate and low level of formality, respectively. In terms of collocations, ‘fate’ and ‘destiny’ share some identical verbs (i.e., await, determine, escape) and adjectives (i.e., inevitable, tragic, ultimate), confirming their synonymy. However, the analysis of the semantic preferences of verb and adjective collocates shows both overlapping and distinctive semantic subsets. Specifically, ‘fate’ is more likely to pair with other verb and adjective collocates associated with pessimism (i.e., bemoan, curse, terrible, uncertain), in contrast to ‘destiny’, whose verb and adjective collocates semantically represent optimism (i.e., embrace, fulfil, glorious, heroic). Regarding semantic prosody, concordance lines with ‘fate’ primarily carry negative connotations, while those with ‘destiny’ are mostly neutral. In essence, the results confirm the non-interchangeability of these near-synonyms across contexts due to their subtle differences, as informed by the corpus data.